If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m = j + -18 Reorder the terms: -3m = -18 + j Solving -3m = -18 + j Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-3'. m = 6 + -0.3333333333j Simplifying m = 6 + -0.3333333333j
| 13s-19s=18 | | 3y^2+8=36 | | 9y+9=8y-8 | | -5x+34x+7= | | 67n=-22 | | 2p^3+p^2q+pq= | | -5p+2+6p=9 | | -694=.83r | | 2x^2+27x-5.1=0 | | -.125x=-4 | | .1b=-108 | | 3(4z-1)-5(z+1)=3(z+1) | | 3y-12=7 | | .05=.6m | | 3x^2+4+1= | | -.75k=.67 | | -13x^3+20x-7=0 | | 18=-.5t | | -4d+2(4+9)=-14 | | 0.083n=12 | | 9m-13=-22+8m | | 36y=108 | | x^3-x^2-1120=0 | | x=-3y^2-12y | | 3(x-4)-2(x+2)-13=-20 | | (3x-12)-2x+-2-13=-20 | | 3x-12-2x+4-13=20 | | 24x^3-21x^2= | | (3x-12)-2x+(-2)-13=-20 | | -4=8-s | | 2-(y+2)=y | | 46x^3+43x^2+5x= |